UJI TOKSISITAS AKUT MINUMAN PROBIOTIK SIRSAK GUNUNG (Annona montana Macf.) DENGAN METODE BSLT (Brine Shrimp Lethality Test) - Ambar Fidyasari; Sentot Joko Raharjo; Melani Setyowati (Sekolah Tinggi Pariwisata Mataram, 2020)
Soursop fruit (Annona montana Macf.) is one of the plants can be used as as traditional medicine. This plant contains terpenoid and acetogenin which can cause toxicity. The fruit has a flavor that is tasteless so the innovation becomes probiotic drinks. This drink has been proven as an antioxidant, antibacterial, antihyperuricemia and antidiarrheal. The aim of this study was to know about acute toxicity of probiotic drink of soursop juice using brine shrimp lethality test method which will be indicated by LC50 value. This study used experimental methods conducted in the Laboratory of Farmakoknosi. There are several variations in concentration in this study, namely 10000 ppm, 20000 ppm, 30000 ppm, 40000 ppm, 50000 ppm, 60000 ppm, 70000 ppm, 80000 ppm and replication was done 3 times with total number of test animals used was 270. The results showed that probiotic drink of soursop juice can provide acute toxic effects on test animals with LC50 value of 29717,23 ppm. LC50 values ​​indicate that the mountain soursop probiotic drink is not potentially toxic because it has a value of >1000 ppm.